Non-Financial Disclosure and Integrated Reporting : Practices and Critical Issues. - Songini, Lucrezia; Pistoni, Anna; Baret, Pierre; Kunc, Martin H. (Studies in Managerial and Financial Accounting Ser., 2020)
For researchers and managers interested in performance measurement, this volume includes innovative research that sheds light on topics such as the determinants of disclosure quality, the identification of appropriate metrics, the relationship among the different disclosure mechanisms and between voluntary and mandatory disclosure, and many more.